Significance of Transport Immobilisation of Tibia and Ankle Fracture in Case of Pregnant Women and Other Injured Persons - Trošelj, Željko; Zovak, Goran; Premužić, Ivica (Promet - Traffic&Transportation, 2004)
The analysis of the data from the case history of patientswith tibia and ankle fractures was carried out to show the significanceof identifying such conditions and the consequent implementationof transporl immobilisation as the first step intreating the injured persons. The implementation of transporlimmobilisation in indicative conditions should be imperativein providing first aid regardless of who is providing it (a laymanor a medically educated person). The tibia and ankle fracturesare easily identifiable and it is not difficult to diagnose them.The data that have been gathered lead to considering thelevel of education or negligence of the participants included inthe first aid chain. Taking into consideration the facts that thenumber of traffic accidents is increasing in the world, thatCroatia is at the very top of the list regarding the number of fatalitiesper capita, that the timely and properly provided first aidreduces the frequency of complications of the injury itself, thuscausing the reduction of the treatment costs, in our opinion immobilisationas one of the aspects of providing first aid did notlose its actual significance, but acquired additional significancewithin the framework of increased and higher-quality possibilitiesof providing first aid.